Food and feeding patterns of the southern brown shrimp Penaeus subtilis Perez-Farfante, 1967 (Crustacea, Penaeidae) - Nunes, Alberto Jorge Pinto (1999)
Penaeid shrimp farming constitutes the most important aquaculture sector in economic value. In recent years however, the activity has faced slower progress in production despite a rapid intensification of production methods. The description and quantification of the food and feeding patterns of cultured penaeids may improve resource-use efficiency and conserve inputs critical to the sustainability of the activity. -- This thesis investigated the food and feeding patterns of Penaeus subtilis under laboratory-controlled and culture conditions. Video-recording of shrimp feeding behaviours was used to examine food handling efficiency and size selectivity. Shrimp feeding levels in response to food dispersal method were determined through quantitative analysis of stomach contents and stable carbon isotope mass spectrometry. The abundance of polychaetes was used to study the effects of shrimp predation, stocking density and supplemental feeding. Partial integration of data was carried out using STELLA® II. -- Results indicated that Penaeus subtilis feed manipulation was inversely related to food particle size, with large pellets being less preferred than small ones. Within the feed size range examined, shrimp size had no significant effect on handling efficiency. Feed broadcasting was a more effective method in regards to shrimp food intake, resulting in a greater access and a higher consumption of food among the cultured shrimp population, a lower number of empty stomachs and a greater occurrence of feed in P. subtilis diet. Ingestion of food was a function of shrimp body weight. Feeding intensity increased progressively with shrimp size, but inversely in percentage terms. Foregut clearance rates peaked 3 h after food recovery, while the bulk of faeces was produced within 1 h. Polychaete abundance was affected by higher shrimp stocking densities. Artificial feeding promoted higher polychaete levels, although was not capable of alleviating shrimp grazing pressure at increased stocking densities. -- Results indicated that crumbles and broken pellets may be more advantageous in the culture of Penaeus subtilis. Feeds should be broadcast evenly over the culture area and administered regularly at continually reduced amounts. Rations should vary in accordance to estimates of P. subtilis body weight and account for the initial polychaete abundance and shrimp stocking densities.